Candiduria: up-to-date review - doi:10.5020/18061230.2011.p142 - Rodrigues, Daniela (2012)
Objective: To summarize the current knowledge about candiduria, describing the epidemiology in Brazil and worldwide, pathogenesis, laboratorial diagnosis and prescribed therapy. Data Synthesis: A non-systematic review carried out from the databases: Pubmed, Cochrane and Scielo in scientific articles related to the theme candiduria and published in the last twenty years. The terms “candiduria”, “Candida” and “hospital infection” were used as descriptors, individually or in association. Articles that addressed other types of Candida infection or were not suitable for the aim of the study were excluded. The studies reviewed indicate that the most prevalent species are in descending order Candida albicans, C. parasilosis, C. tropic alis, C. glabrata, C. krusei, C. guilliermondii, C. lusitaniae, C. dubliniensis, C. kefyr and C. rugosa. When treatment is indicated, the drug of choice is fluconazole, provided that the isolates do not possess intrinsic resistance. Conclusion: Despite its high incidence and clinical relevance, the candiduria is not yet been fully elucidated, remaining the need to clarify its epidemiology and pathogenesis in emerging species and reach consensus on treatment protocols.